2020
DOI: 10.1002/jsfa.10280
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different drying processes on the lipid deterioration and color characteristics of Penaeus vannamei

Abstract: BACKGROUND Fresh shrimp (Penaeus vannamei) deteriorates easily and the drying process is an important processing method for prolonging the shelf life of shrimp. The traditional drying method is hot‐air‐drying (HD), which can cause some problems such as nutrient loss, discoloration and lipid oxidation. In recent years, freeze‐drying (FD) has been popular for removing moisture from food at lower temperatures, maintaining the structure of raw materials, and improving storage stability of products. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 36 publications
(67 reference statements)
1
21
0
Order By: Relevance
“…Moreover, the values of color parameters of fresh shrimp were similar to those of the dehydrated shrimp from US15 and US30, which demonstrated that the US and the dehydration temperature (35°C) did not change the color with respect to the fresh shrimp. A study of drying shrimp in a forced convection oven at 60°C showed that the initial L* = 52.30, a* = −0.67, and b* = −0.62 of the fresh shrimp changed to L* = 88.30, a* = 6.14, and b* = 16.82 when boiling the shrimp for 7 min was used as a pretreatment (Li, Zhou, et al., 2020). The increase in a* (redness) of the shrimp meat is due to exposure to heat, which releases astaxanthin when carotenoproteins break down during protein denaturation, while increase in b* (yellowness) is due to the generation of yellow pigments from darkening reactions (Akonor et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the values of color parameters of fresh shrimp were similar to those of the dehydrated shrimp from US15 and US30, which demonstrated that the US and the dehydration temperature (35°C) did not change the color with respect to the fresh shrimp. A study of drying shrimp in a forced convection oven at 60°C showed that the initial L* = 52.30, a* = −0.67, and b* = −0.62 of the fresh shrimp changed to L* = 88.30, a* = 6.14, and b* = 16.82 when boiling the shrimp for 7 min was used as a pretreatment (Li, Zhou, et al., 2020). The increase in a* (redness) of the shrimp meat is due to exposure to heat, which releases astaxanthin when carotenoproteins break down during protein denaturation, while increase in b* (yellowness) is due to the generation of yellow pigments from darkening reactions (Akonor et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…At present, drying and freezing processes are the main methods applied to preserve shrimp and other aquatic products, but the freezing process needs a more elevated initial investment and higher costs of manufacture and conveying (Olvera Ríos et al., 2020). However, drying is preferred due to its high level of efficiency, easy functioning, and economical investing costs (Li, Zhou, et al., 2020; Nguyena et al., 2019), in addition to the advantages of prevention of spoilage of foods by reduction of a w , as well as the production of materials with weight and volume lower to make storage and transportation easier (Hu et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that UFAs degrade into aldehydes, ketones, and lower fatty acids during the lipid oxidation process [8,9]. ω-3 PUFAs are susceptible to peroxidation because of free radicals, resulting in an unpleasant odor and potentially toxic biological effects [10]. Lipid oxidation was evaluated by measuring hydroperoxides and conjugated dienes, revealing the mechanism of producing thiobarbituric acid (TBA) oxidation products [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Drying preserves mushrooms by removing moisture from the raw materials and allows the product new features different from fresh ones 1,6,7 . Currently, hot air drying (HD) and vacuum freeze‐drying (VFD) are the most widely used drying techniques in the food industry 8–10 . The main advantages of HD are low costs, high yields, and simple operations, but, simultaneously, the dried products are at risk of losing visual appearance and thermolabile nutrients 11,12 .…”
Section: Introductionmentioning
confidence: 99%